Analysis of Batik Marketing Management in South Tapanuli Regency - Nur Mutiah; Ali Hardana; Try Wahyu Utami (CV. AFDIFAL MAJU BERKAH, 2023)
Sipirok Batik Village is one of the cultural areas in Indonesia which is rich in cultural and historical potential that has been inherited from our ancestors. One of the invaluable heritages owned by the Sipirok batik village is the art of batik which is included in the intangible cultural heritage. Solo batik art, which is the main attraction, is enriched with historical sites such as historic tombs and mosques and other sites. The aims of this research are to: (1). Analyzing marketing management carried out by batik entrepreneurs in Sipirok Batik Village, South Tapanuli Regency, (2). To find out the marketing management carried out by batik entrepreneurs in Sipirok Village, South Tapanuli Regency, (3). To find a new marketing management so that it can further increase batik sales in Sipirok Batik Village, South Tapanuli Regency, (4). This research is expected to be able to contribute to the government to encourage local governments to support the preservation of batik. The research results are: (1). The research planned by the researchers has been successfully implemented in the Sipirok Batik Village, South Tapanuli Regency, (2). The results of data processing show that the marketing carried out by the batik artisans of Kampung Batik Sipirok, South Tapanuli Regency still uses traditional methods as much as 17%, while marketing management is carried out by batik craftsmen using ICT (website) as much as 83%, (3). Based on the SWOT analysis, it can be concluded that the marketing management marketing method that uses internet technology (website) can be applied by batik craftsmen in Sipirok Batik Village, South Tapanuli Regency.